Hubungan Antara Risiko Sistematis, Tingkat Suku Bunga, dan Return Saham dalam Portofolio Investasi: Analisis pada Bank BUMN yang Terdaftar di BEI - Banafsyah Imanda Safa; Diana Oktavia Kholimah Wati; Vidinia Nuansa Citra; Felisya Natalia Purwanto; Maria Yovita R. Pandin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to examine the impact of systematic risk and interest rates on the stock returns of state-owned banks (Bank BUMN) listed on the Indonesia Stock Exchange during the period 2021–2023. Using a multiple linear regression approach, the study finds that neither systematic risk nor interest rates have a significant partial or joint effect on the stock returns of Bank BUMN. These findings indicate that in the context of the Indonesian stock market—particularly the state-owned banking sector—these factors may not necessarily be the primary determinants in shaping stock returns. The implication of these results is the importance of considering other variables that may play a greater role in explaining stock return movements, such as firm-specific microeconomic factors and investor expectations regarding the banks’ fundamental performance.